The Effects of Superstitious Thoughts on the Older Adults’ Lifestyle - Fatemeh Motlagh; Abdolrahim Asadollahi; Laleh Fani Saberi; Ehteram Sadat Ilali; Najmeh Hosseini (Journal of Health Sciences and Surveillance System, 2024)
Background: A society’s culture, beliefs, and values are important and effective factors in lifestyle and health status. Therefore, this study aimed to determine the correlation between older adults’ tendency towards superstitions and their healthylifestyles.Methods: This study was descriptive-analytical and of a correlational type. The statistical population consisted of all the older adults covered by healthcare centers in the North of Iran. The sample size was determined to be 360 using the multistage random sampling method. Data were collected using the Elderly Healthy Lifestyle and Tendency to Superstitions Questionnaires. Spearman’s test, regression analysis, chi-square, Kruskal-Wallis tests, and SPSS 28 software were utilized to analyze the data.Results: Among a total of 360 elderly participants in the study, 173 were male, and 187 were female, in the age range of 60 to 91 years. The results indicated a significant correlation (P<0.001) with an effect size of 29% between superstitions and a healthy lifestyle. According to the findings, the regression model fitted with the predictive variable, superstitions, could explain 14% of the variance in the dependent variable, lifestyle.Conclusion: The research results emphasized that the tendency towards superstitions could be a predictive and effective factor in older adults’ healthy lifestyles.